Changes in the functional capacity of active and institutionalized elderly - Gomes,Igor Conterato (2020)
ABSTRACT This study aimed to observe changes in the functional capacity of the elderly. Eighteen elderly individuals (mean 74.3 years) were divided into two groups: water aerobics (GH, n = 08) and institutionalized (GI, n = 10). Functional capacity was identified through the battery of tests proposed by Rikli and Jones (1999). After the intervention period, both groups showed reductions in the valences evaluated. However, in GI the reductions were more accentuated. For Cardiorespiratory Capacity, Mobility, and Strength of lower limbs, there were reductions for GH of (−4.22%, −9.42%, and −19.23%) and GI of (−52.20, −135.43%, and −28%) respectively. For the Time up and Go test (TUG), statistical effect was present for time (with lower time post vs. pre; p = 0.021) as well as a significant interaction for time*group (p = 0.027), respectively. Physical exercise programs for the elderly can reduce the rate of decline in functional capacity, with healthier aging.